Evaluation of Protectivity of Aquifer Using Dar – ZarroukParameters in Ikot Ekpene Urban and its Environs - Ikpe, Emem (Optimality, 2024)
The protective ability of hydrogeological units in the southern Nigerian region of Ikot Ekpene Urban and its environs was assessed in this work using the resistivity approach, namely vertical electrical sounding and electrical resistivity tomography techniques. The lithological data from boreholes available indicates that the research region consists of three to four sandy strata (fine, coarse, and gravelly) with clay intercalations in some locations. With resistivity values ranging from 214.4 to 2839.0 Ωm, the third layer can be classified as gravelly sands in certain places or fine or coarse sands in other. Found between 9.0 and 86.6 meters below the surface, this layer is the main aquifer in the area. Using anisotropy coefficients, resistivity reflection, and longitudinal conductance, the aquifer protectivity was evaluated. Four zones are formed within the research area based on the protectivity grade. Regarding the proportion of exploitable aquifers, the zones are classified as poor (65%), weak (10%), moderate (20%), and good (5%). The surface topography affects the water table, and in the center of the region a sinkhole develops. Utility pipes may be buried safely inside the stratum without fear of corrosion-induced damage because the heterogeneous topsoil has been shown to be noncorrosive. These results provide important new information for creating a successful groundwater and waste disposal plan in the area.